Surgical Treatment of Posterior Communicating Artery Aneurysms: Hints and Precautions for Young Cerebrovascular Surgeons - Sturiale, Carmelo Lucio; Marchese, Enrico; Puca, Alfredo; Olivi, Alessandro; Albanese, Alessio (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Background In spite of the advent of neurointerventional treatment, different clinical and anatomical features are still strong indications for clipping of posterior communicating artery (PComA) aneurysms. But the experience of young neurosurgeons is increasingly limited, and therefore providing technical operative guidelines is a fundamental prerequisite to achieve the best aneurysm exclusion and avoid perioperative complications.Study Objective We describe a technical algorithm we use to teach young neurosurgeons how to approach carotid aneurysms that may help them develop a procedural memory and thus perform an efficient and safe surgery.Material and Methods We reviewed our last 10 years of institutional experience of > 150 cases of clipping ruptured and unruptured PComA aneurysms, analyzing our technical refinements and the difficulties in teaching residents and young neurosurgeons how to establish fundamental key points and design a didactic algorithm that includes operative instructions and safety rules.Results We recognized seven pragmatic technical key points regarding craniotomy, cisternostomy, proximal and distal control, aneurysm neck dissection, preservation of neurovascular structures, and clipping to use in a didactic algorithm for teaching residents and as operative instructions for inexperienced neurosurgeons.Conclusion In the setting of clipping PComA aneurysms, respect for surgical rules is of paramount importance to perform an efficacious and safe procedure and ensure the best aneurysm exclusion and preservation of neurovascular structures.
Keywords: posterior communicating artery aneurysm; PComA aneurysms; lateral supraorbital approach; clipping; third cranial nerve preservation